Do non-human primates really represent others’ ignorance? A test of the awareness relations hypothesis - Horschler, Daniel J. (Cognition, 2019)
Non-human primates can often predict how another agent will behave based on that agent’s knowledge about the world. But how do non-human primates represent others’ knowledge states? Researchers have recently proposed that non-human primates form “awareness relations” to attribute objectively true information to other minds, as opposed to human-like representations that track others’ ignorance or false belief states. We present the first explicit test of the awareness relations hypothesis by examining when rhesus macaques’ understanding of other agents’ knowledge falters. In Experiment 1, monkeys watched an agent observe a piece of fruit (the target object) being hidden in one of two boxes. While the agent’s view was occluded, either the fruit moved out of its box and directly back into it, or the box containing the fruit opened and immediately closed. We found that monkeys looked significantly longer when the agent reached incorrectly rather than correctly after the box’s movement, but not after the fruit’s movement. This result suggests that monkeys did not expect the agent to know the fruit’s location when it briefly and arbitrarily moved while the agent could not see it, but did expect the agent to know the fruit’s location when only the box moved while the agent could not see it. In Experiment 2, we replicated and extended both findings with a larger sample, a different target object, and opposite directions of motion in the test trials. These findings suggest that monkeys reason about others’ knowledge of objects by forming awareness relations which are disrupted by arbitrary spatial manipulation of the target object while an agent has no perceptual access to it.